Pregnancy outcomes in women with tuberculosis: a 10-year experience from an Indian tertiary care hospital. (April 2017) - Chopra, Seema; Siwatch, Sujata; Aggarwal, Neelam; Sikka, Pooja; Suri, Vanita
Our study sought to determine the characteristics of antenatal patients with tuberculosis (TB) and their pregnancy outcomes. Case records of 50 antenatal women with extra-pulmonary and pulmonary TB at a tertiary centre in India were compared to 150 antenatal women not suffering from TB, for adverse medical, obstetric and neonatal outcomes. The prevalence of TB was 1.16 per 1000 deliveries. Of these, 62% had extra-pulmonary TB. There were two maternal deaths. TB in pregnancy was associated with a five times higher risk of prematurity and three times higher risk of intrauterine growth restriction than the norm. Maternal prognosis depends on the complications of tuberculosis and treatment compliance.